Pengembangan Strategi Pemasaran Menggunakan Analisis SWOT Pada Kemeja Batik Equatik - Amanda, Meistriya; Arif, Muhammad (Universitas Muhammadiyah Surakarta, 2026)
Indonesia has a rich diversity of local cultures, one of which is batik. Amid fashion trends, creativity and innovation are essential to support the preservation and development of the creative industry. Today, the younger generation also needs to take part in efforts to preserve local culture, including batik. As a preservation effort, Equatik Batik Shirts are introduced by combining modern batik patterns while still prioritizing local cultural values. This research aims to develop marketing strategies for Equatik Batik Shirts to increase public awareness and present batik in a different light. The study uses a SWOT analysis method, which identifies strengths, weaknesses, opportunities, and threats as a basis for making better marketing strategy decisions. The results of this study show that Equatik Batik Shirts is in an aggressive strategy position, which means optimizing its strengths and opportunities in its development.